Optimisation of heating uniformity for milk pasteurisation using microwave coaxial slot applicator system - Abdullah, S.N. (Academic Press, 2022)
Microwave heating is a novel solution for milk pasteurisation but the non-uniformity of thermal distribution is still a significant problem that hampers its application especially for milk pasteurisation. This paper reports on the isotherm heating of a coaxial slot antenna applicator with a microwave signal generation using a fabricated mono-mode microwave system designed to improve the temperature uniformity of batch milk pasteurisation. In this paper, applicator simulation, design, characterisation, and fabrication are described in detail. The fabricated microwave pasteurisation system was implemented using a digitally controlled water-cooled magnetron with a waveguide circulator, a three-screw waveguide tuner, a water-based waveguide terminator, and a rectangular to coaxial adapter to channel the output. The impedance matching and power calibration routines of the fabricated microwave pasteurisation system are explained and analysed in detail. Three microwave powers, namely 100 W, 125 W and 150 W were used to test and characterise the pasteurisation performance of the system. For each microwave power the thermal profile and the temperature distribution of the 100 ml milk samples in a glass beaker were simulated and measured. The pasteurisation process was evaluated based on the aerobic plate count (APC) test. Results showed 90 improvement in the temperature uniformity as compared with an existing batch microwave pasteurisation method. The APC test showed pasteurisation efficiency was 99.999 and total microbial elimination occurred after 7 min, 6 min, and 5 min of heating using 100 W, 125 W, and 150 W power respectively. Â© 2022 IAgrE